Engineering properties of cemented peat bricks - Deboucha, Sadek; Hashim, Roslan; Abdul Aziz, Azlan (Academic Journals, 2011)
Housing is a great problem in today’s world and the world future. The most basic building material for infrastructure construction and housing is the usual brick or blocks. Conventional bricks, which are burnt clay, create environmental problems. The purpose for this study was undertaken on the production of peat; siliceous sand, composite cement and lime solid bricks to solve the economic problems of housing and construction building by utilizing local materials. The compressive strength, water absorption and density of these bricks were investigated. It was observed that these bricks had sufficient strength for their use in low cost housing development. Tests were also conducted to study the influence of curing type on the increase in strength and hardening of the bricks with time.